Nierównowaga rynkowa a kryzys gospodarczy - Fiedorowicz, Kazimierz (Market Imbalance and the Economic Crisis, 2009)
The article discusses the influence of the market imbalance on the threat of occurrence of the economic crisis taking into consideration the influence of changes of condition-dependent and secular cycles. The market imbalance loops the loop. In comparison with condition-dependent and secular cycles, the looping causes the deepening of the economic crisis. Introduced technological changes weaken the threat of occurrence of the crisis. At the moment, the Polish economy is in the state of imbalance which deepens the economic crisis in the present period of a weaker condition-dependent cycle. A counteraction against the deepening crisis is reducing the share of expenses from the country's budget in GNP. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 97-106